2016
DOI: 10.14202/vetworld.2016.1087-1101
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular identification of the brown dog tick Rhipicephalus sanguineus and the camel tick Hyalomma dromedarii (Acari: Ixodidae) vectors of Rickettsioses in Egypt

Abstract: Aim:Rickettsioses have an epidemiological importance that includes pathogens, vectors, and hosts. The dog tick Rhipicephalus sanguineus and the camel tick Hyalomma dromedarii play important roles as vectors and reservoirs of Rickettsiae. The aim of this study was to determine the prevalence of Rickettsiae in ixodid ticks species infesting dogs and camels in Egypt, in addition to, the morphological and molecular identification of R. sanguineus and H. dromedarii.Materials and Methods:A total of 601 and 104 of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 90 publications
4
38
0
Order By: Relevance
“…However, the detection of SFG rickettsiae in the present study indicated the possibility for these pathogens to be present in dogs and horses in Egypt, and the importance of these domestic animals as potential infection amplifiers which play a more dominant role in the persistence of rickettsiae in the nature than previously thought [2,7]. Hence, the detection of tick-borne rickettsiae in dogs and their ticks in the previous studies indicated that both the animal and human populations in Egypt are at risk for these pathogens [19]. In addition to, Rh.…”
Section: Primer Amplifying Sequence Of Rickettsiae Wassupporting
confidence: 57%
See 2 more Smart Citations
“…However, the detection of SFG rickettsiae in the present study indicated the possibility for these pathogens to be present in dogs and horses in Egypt, and the importance of these domestic animals as potential infection amplifiers which play a more dominant role in the persistence of rickettsiae in the nature than previously thought [2,7]. Hence, the detection of tick-borne rickettsiae in dogs and their ticks in the previous studies indicated that both the animal and human populations in Egypt are at risk for these pathogens [19]. In addition to, Rh.…”
Section: Primer Amplifying Sequence Of Rickettsiae Wassupporting
confidence: 57%
“…The PCR reactions were performed in a PTC-100™ thermal cycler (MJ Research Inc., USA) under complete aseptic condition. The protocol of the reactions was applied according to Abdullah et al [19]. PCR products were visualized by electrophoreses in 1.5% agarose stained with ethidium bromide.…”
Section: Screening Of Rickettsiae By Pcr Using Ompa Genementioning
confidence: 99%
See 1 more Smart Citation
“…A total of 113 camels were examined for the presence of ticks on different parts of their bodies according to Abdullah et al . [ 25 ] from Cairo, Giza, and Sinai in Egypt during the period from June to August 2017. Blood samples with ethylenediaminetetraacetic acid (EDTA) (5 ml each animal) were collected from jugular veins and were stored at −20°C for molecular purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Standard PCR was applied to confirm MALDI-TOF identification. Mitochondrial genes (CO1 and 16S rRNA gene) sequencing was used for the identification of flies and tick species through DNA automated thermal cycler (Applied Biosystem, Paris, France) under the same condition as previously described (Table 1) [48,49]. PCR products were purified and sequenced as mentioned earlier [48].…”
Section: -Molecular Identification Of Vectorsmentioning
confidence: 99%